Wide-range and sensitive detection of LPS using a transporter@liposome enhanced electrochemical aptasensor - Xinyu Hu; Shukai Song; Ruyu Lin; Weidong Zheng; Haochen Qi; Lin Xu; Jian Zhang (Analytica Chimica Acta, 2026)

Beyond correlation: Unveiling the causal link between streetscapes and recreational walking/cycling - Lingzi Xu; Haochen Shi; Wenbo Lyu; Yan Zhang; Hongbo Zhao (Journal of Transport Geography, 2026)

Three-dimensional printed zerovalent iron enables selective and sustained reductive dehalogenation of florfenicol via structure-induced corrosion resistance and electron transfer regulation - Dan Li; Lu Liu; Haochen Li; Tao Ye; Junhong Wu; Jiaying Li; Si Zhai; Mengli Li; Huigai Wei; Lei Li; Jianhui Xu; Peng Liu; et al. (Environmental Research, 2026)

A bounding surface model for methane hydrate-bearing sediment incorporating hydrate dissociation - Lujun Wang; Dongyu Yang; Haoqi Song; Haochen Yang; Linfang Xu; Bo Ning; Bin Zhu (Computers and Geotechnics, 2026)

Dabie mountain topography and cross-regional transport regulating nitrate heterogeneity during a severe haze episode in Jiangxi - Haochen Zuo; Mingxuan Xu; Yangfan Jin; Kangjia Gong; Xiang Tu; Yao Wang; Xiaodong Xie; Jiao Wang; Jianlin Hu (Atmospheric Environment, 2026)

Hydrogen radical is also a critical reductive defluorination species in the Far-UVC-activated sulfite process - Xiangyang Hou; Shu Xu; Qiuling Lu; Kai Wang; Haonan Lu; Haochen Zhang; Yuying Li; Minchao Liu; Jin Jiang; Shuo Li; Jun Ma; Tiangang Luan; et al. (Journal of Hazardous Materials, 2026)

ConsenNet–based fully decentralized MARL for residential flexibility coordination in resilient community microgrids - Peixian Huang; Cheng Ma; Mingze Xu; Haochen Hua; Jin Zhao; Shunbo Lei (Energy and Buildings, 2026)

Solar light irradiation activated dichloramine for efficient abatement of micropollutants - Peng Su; Wenjun Zhang; Haochen Zhang; Haonan Lu; Qiuling Lu; Kai Wang; Yuying Li; Xiaolong Xu; Changyu Liu; Jun Ma; Tao Yang (Water Research, 2026)

Ultrasound-activated azido-sulfonamide prodrug nanoparticle with antibacterial peptide targeting for selective bacterial infection therapy - Jiali Sun; Jiahui Pan; Xitong Ren; Zecheng Chang; Wenfang Wang; Guoqing Wang; Jianting Xu; Jianshi Du; Haochen Yao (Chemical Engineering Journal, 2026)

Dairy flavor measurements from materials to human perception: Emerging trends and applications - Yangfan Guo; Ying Wang; Haochen Zhou; Xinying Xu; Dongxiao Sun-Waterhouse; Shan Ding; Fanyu Meng; Tao Jiang; Bei Wang (Trends in Food Science & Technology, 2026)

Comparative study of promising CaAl-LDH and conventional immobilizing agents in mitigating ecological and health risks associated with soil Pb contamination - Jianying Yu; Nan Wei; Haochen Fang; Yining Chen; Tengfei Guo; Qijia Zhang; Yangyang Chen; Jiahong Yu; Jianyu Zhang; Zeliang Han; Kaiqin Xu; Ching Yuan; et al. (Journal of Environmental Management, 2026)

Why same datasets yield different environment–activity relationships? Hidden uncertainties in geospatial processing methods - Haochen Shi; Lingzi Xu; Ding Ma; Feng Gao; Shaoying Li (Computers, Environment and Urban Systems, 2026)

Characterization of Interlayer Resistivity Responses in Crack-Containing Rock-Like Materials and Analysis of Failure Precursors - Tingye Qi; Hongtao Xu; Guorui Feng; Tian Qiu; Haochen Wang; Linfei Wang; Siyuan Cheng; Xinkai Qi; Lubin Li (Rock Mechanics and Rock Engineering, 2026)

A green approach for the selective recovery of Copper, Lead, and Tin from End-of-Life photovoltaic solder ribbons - Shun Dai; Shiyu Wang; Haochen Wang; Fengyin Zhou; Simin Xu; Yongxin Wu; Muya Cai; Xinyi Li; Shuaibo Gao; Wei Li; Bowen Deng; Dihua Wang; et al. (Waste Management, 2026)

Close-packed metal organic frameworks enabled high-energy solid-state lithium metal batteries - Yining Zhang; Hongsheng Shi; Yuyao Zhang; Xin Chen; Shuanghong Wang; Jinjiang Liang; Qiong Yuan; Tianyi Gao; Ran Wei; Haochen Zhang; Tao Li; Tianquan Lin; et al. (Chemical Engineering Journal, 2026)

New insight into acidic fluoride removal by tannic acid-mediated cerium oxides: Performance and mechanism - Haochen Wang; Menghan Huang; Zhe Xu; Hui Qiu (Chemical Engineering Journal, 2025)

Multi-cation system in spent lithium-ion batteries leaching solution: a pathway to lithium-selective via nanofiltration - Zihan Xu; Chunchun Meng; Yanhui Wu; Xinwu Li; Xinyu Zeng; Guangming Li; Haochen Zhu (Desalination, 2025)

MobileYOLO-Cyano: An enhanced deep learning approach for precise classification of cyanobacterial genera in water quality monitoring - Yang Tao; Hamed Karimian; Juan Shi; Haochen Wang; Xuchu Yang; Yanchang Xu; Yi Yang (Water Research, 2025)

Mitigating overestimation in lithium-ion battery recycling LCA: The critical role of ex-post data and operational parameters - Shiyu Wang; Fengyin Zhou; Jingjing Zhao; Hongya Wang; Xin qu; Muya Cai; Haochen Wang; Xu Wang; Dihua Wang; Huayi Yin (Chemical Engineering Journal, 2025)

Enhancement of nitrogen and phosphorus removal from municipal wastewater treatment plant effluents by iron-modified solid carbon source in constructed wetlands: Performance and mechanism - Haochen Shi; Jinlong Zhuang; Wei Wu; Mingjun Sheng; Haifang Pei; Xiaoyi Xu; Tianyin Huang (Chemical Engineering Journal, 2025)

Global real-time PPP using Galileo HAS compared with WHU RTS - Xiaodong Ren; Haochen Yang; Guozhen Xu; Ke Yao; Yuxin Zhang; Xiaohong Zhang (Advances in Space Research, 2025)

Optimizing performance and stability in textured 2 T perovskite/silicon tandem photovoltaic devices through self-assembled monolayer-mediated doping strategies - Rui Li; Jungan Wang; Huiwei Du; Chenghao Song; Haochen Zhang; Menglei Xu; Peiting Zheng; Xinyu Zhang; Jie Yang; Chengjun Gu; Qin Zou; Jingji Zhang; et al. (Chemical Engineering Journal, 2025)

Crystalline carbon nitride derived self-assembly composite membranes with enhanced self-cleaning performance toward dye/salt separation - Yujing Qiu; Haochen Xu; Ying Zhou; Beizhao Chen; Zhongying Wang; Yi Yang; Qile Fang; Ying Mei (Journal of Environmental Management, 2025)

Adsorption kinetics of different mercury species on three kinds of micro-/nano-plastics in micro-polluted aquatic environments and their combined toxicity - Siqi Wu; Chen Yang; Haochen Xu; Yiwei Zhu; FengFu Fu; Yue Lin (Science of The Total Environment, 2025)

Mechanism of enhanced oil recovery via carbon dioxide flooding in kerogen nanopores: A molecular dynamics approach - Yiqun Zhang; Yiquan Jiang; Jing Zhang; Haochen Huang; Tianyu Wang; Jinshan Wang; Yingqiao Ren; Xu Cui (Fuel, 2025)

AI-Driven urban planning optimization: A graph neural network and genetic algorithm framework for tackling peak-hour challenges - Jianyi Li; Yin Zhang; Shuo Yu; Haochen Qin; Zhen Xu (Sustainable Cities and Society, 2025)

Facility of tomato plant organ segmentation and phenotypic trait extraction via deep learning - Jiangjun Yao; Yan Gong; Zhengyan Xia; Pengcheng Nie; Honggang Xu; Haochen Zhang; Yufei Chen; Xuehan Li; Zhe Li; Yiming Li (Computers and Electronics in Agriculture, 2025)

In vitro induction and characterization of octaploid Schizachyrium scoparium, an ornamental grass - Zhuolin Xiao; Mingjun Wei; Yue Xu; Haochen Nie; Hui Zhang; Ke Teng; Wenjun Teng; Juying Wu; Xifeng Fan; Yuesen Yue (Plant Cell, Tissue and Organ Culture (PCTOC), 2025)

Investigation on the rejection of mixed salt solution by g-C3N4 functionalized nanofiltration membrane - Zihan Xu; Zhaohuan Mai; Yanhui Wu; Xinwu Li; Xinyu Zeng; Chunchun Meng; Guangming Li; Haochen Zhu (Desalination, 2025)

Human behavior-based COVID-19 transmission in two dining spaces - Zhikang Xu; Haochen Zhang; Min Zhu; Ying Ji; Peng Xue; Jingchao Xie; Yuguo Li; Nan Zhang (Journal of Hazardous Materials, 2024)

Machine Learning-Driven Precise Design of Stable OLED Materials: Predicting and Enhancing Multi-State C-N Bond Dissociation Energies - Yiming Shi; Haochen Shi; Haichang Wang; Chun-Jung Chen; Yaoyao Li; Bo Qiao; Zhiqin Liang; Suling Zhao; Deyu Hang; Zheng Xu; Dandan Song (Chemical Engineering Journal, 2024)

Insight into adsorption behaviors of shale oil in kerogen slit by molecular dynamics - Yiqun Zhang; Yiquan Jiang; Qiang Wei; Haochen Huang; Tianyu Wang; Hao Xiong; Jinshan Wang; Yingqiao Ren; Xu Cui (Fuel, 2024)

Burning behavior of hydrogen jet flame inhibited by a wire mesh screen - Zhenhua Tang; Zhirong Wang; Hui Xu; Yuhan Xiao; Haochen Lu; Kun Zhao (Process Safety and Environmental Protection, 2024)

Machine learning-enabled discovery of multi-resonance TADF molecules: Unraveling PLQY predictions from molecular structures - Haochen Shi; Yiming Shi; Zhiqin Liang; Suling Zhao; Bo Qiao; Zheng Xu; Lijuan Wang; Dandan Song (Chemical Engineering Journal, 2024)

Cascading H2O2 photosynthesis and Fenton reaction for self-sufficient photo-Fenton reactions: A review of recent advances - Maoquan Wu; Xu Guo; Yaodan Cao; Haochen Yu; Zherui Hu; Yang Yang; Tongjie Yao; Jie Wu (Chemical Engineering Journal, 2024)

Carbon slow-release and enhanced nitrogen removal performance of plant residue-based composite filler and ecological mechanisms in constructed wetland application - Zhaoyang Li; Tianyin Huang; Wei Wu; Xiaoyi Xu; Bingdang Wu; Jinlong Zhuang; Jingjing Yang; Haochen Shi; Yang Zhang; Bin Wang (Bioresource Technology, 2024)

State-Transform MPC-SMC-Based Trajectory Tracking Control of Cross-Rudder AUV Carrying Out Underwater Searching Tasks - Haochen Hong; Zhiqiang Yang; Jiawei Li; Guohua Xu; Yingkai Xia; Kan Xu (Journal of Marine Science and Engineering, 2024)
In this study, we present a novel dual-loop robust trajectory tracking framework for autonomous underwater vehicles, with the objective of enhancing their performance in underwater searching tasks amidst oceanic disturbances. Initially, a real-world AUV experiment is conducted to validate the efficacy of a cross-rudder AUV configuration in maintaining sailing angle stability during the diving stage, which exhibits a strong capability for straight-line sailing. Building upon the experimental findings, we introduce a state-transform-model predictive guide law to compute the desired velocity for the dynamics loop. This guide law dynamically adjusts the controller across varying depths, thereby reducing model predictive control (MPC) computation while optimizing timing without compromising precision or convergence speed. Subsequently, we incorporate a sliding mode controller with a prescribed disturbance observer into the velocity control loop to concurrently enhance the robustness and convergence rate of the system. This innovative amalgamation of controllers significantly improves tracking precision and convergence rate, while also alleviating the computational burden—a pervasive challenge in AUV MPC control. Finally, various condition simulations are conducted to validate the robustness, effectiveness, and superiority of the proposed method. These simulations underscore the enhanced performance and reliability of our proposed trajectory tracking framework, highlighting its potential utility in real-world AUV applications.

Exploring the ecological meanings of temperature sensitivity of ecosystem respiration from different methods - Yang Zhang; Gaofeng Zhu; Kun Zhang; Heng Huang; Liyang He; Cong Xu; Huiling Chen; Yonghong Su; Yuzhong Zhang; Haochen Fan; Boyuan Wang (Science of The Total Environment, 2024)

Energy partitioning over an irrigated vineyard in arid northwest China: Variation characteristics, influence degree, and path of influencing factors - Huiling Chen; Yongtai Zhu; Gaofeng Zhu; Yang Zhang; Liyang He; Cong Xu; Kun Zhang; Jing Wang; Ramamoorthy Ayyamperumal; Haochen Fan; Boyuan Wang (Agricultural and Forest Meteorology, 2024)

Life cycle environmental benefits of recycling waste liquor and chemicals in production of lignocellulosic bioethanol - Yunzi Hu; Haochen Du; Luyao Xu; Cuiyi Liang; Yu Zhang; Zhigang Sun; Carol Sze Ki Lin; Wen Wang; Wei Qi (Bioresource Technology, 2023)

A lightweight deep learning model for ocean eddy detection - Haochen Sun; Hongping Li; Ming Xu; Fan Yang; Qiang Zhao; Cuishu Li (Frontiers in Marine Science, 2023)
Ocean eddies are typical oceanic mesoscale phenomena that are numerous, widely distributed and have high energy. Traditional eddy detection methods are mainly based on physical mechanisms with high accuracy. However, the large number of steps and complex parameter settings limit their applicability for most users. With the rapid development of deep learning techniques, object detection models have been broadly used in the field of ocean remote sensing. This paper proposes a lightweight eddy detection model, ghost eddy detection YOLO (GED-YOLO), based on sea level anomaly data and the “You Only Look Once” (YOLO) series models. The proposed model used ECA+GhostNet as the backbone network and an atrous spatial pyramid pooling network as the feature enhancement network. The ghost eddy detection path aggregation network was proposed for feature fusion, which reduced the number of model parameters and improved the detection performance. The experimental results showed that GED-YOLO achieved better detection precision and smaller parameter size. Its mAP was 95.11% and the parameter size was 22.56 MB. In addition, the test experiment results showed that GED-YOLO had similar eddy detection performance and faster detection speed compared to the traditional physical method.

How low-carbon travel improves travel well-being : Evidence from China - Lijun Yu; Yaogeng Xu; Haochen Shi (Sustainable Production and Consumption, 2023)

Mitogenome analysis reveals predominantly ancient Yellow River origin of population inhabiting Datong agro-pastoral ecotone along Great Wall - Yuqing Yan; Panxin Du; Jihong Zhang; Ruilan Li; Haoquan Bao; Qingli Fang; Ye Gao; Hailiang Meng; Yiran Xu; Haochen Shi; Hailong Yan; Xin Chang; et al. (Molecular Genetics and Genomics, 2023)

The impact of the streetscape built environment on recreation satisfaction: A case study of Guangzhou - Haochen Shi; Lijun Yu; Yaogeng Xu; Yuqi Liu; Miaoxi Zhao (Journal of Transport Geography, 2023)

CFSA-AGD: An accurate crosstalk fluorescence spectroscopic decomposition method for identifying and quantifying FDOMs in aquatic environments - Yuchao Fu; Wanxiang Li; Tianyuan Liu; Zhen Zhang; Haochen Li; Jingran Xu; Meizhen Huang (Science of The Total Environment, 2023)

A Data-Driven Intelligent Prediction Approach for Collision Responses of Honeycomb Reinforced Pipe Pile of the Offshore Platform - Lei Yang; Hong Lin; Chang Han; Hassan Karampour; Haochen Luan; Pingping Han; Hao Xu; Shuo Zhang (Journal of Marine Science and Engineering, 2023)
The potential collision between the ship and the pipe piles of the jacket structure brings huge risks to the safety of an offshore platform. Due to their high energy-absorbing capacity, honeycomb structures have been widely used as impact protectors in various engineering applications. This paper proposes a data-driven intelligent approach for the prediction of the collision response of honeycomb-reinforced structures under ship collision. In the proposed model, the artificial neural network (ANN) is combined with the dynamic particle swarm optimization (DPSO) algorithm to predict the collision responses of honeycomb reinforced pipe piles, including the maximum collision depth (δmax) and maximum absorption energy (Emax). Furthermore, a data-driven evaluation method, known as grey relational analysis (GRA), is proposed to evaluate the collision responses of the honeycomb-reinforced pipe piles of offshore platforms. Results of the case study demonstrate the accuracy of the DPSO-BP-ANN model, with measured mean-square-error (MSE) of 5.06 × 10−4 and 4.35 × 10−3 and R2 of 0.9906 and 0.9963 for δmax and Emax, respectively. It is shown that the GRA method can provide a comprehensive evaluation of the performance of a honeycomb structure under impact loads. The proposed model provides a robust and efficient assessment tool for the safe design of offshore platforms under ship collisions.

Metallurgical performance and structural characteristics of cokes of hypercoal prepared from the mixture of low-rank coal and biomass residue - Jun Zhao; Hong Liu; Haochen Zhang; Xiaolin Song; Haibin Zuo; Guangwei Wang; Zhigao Xu; Ming Wu; Zhenyue Zhang; Ru'an Chi (Fuel, 2023)

Numerical Investigation on Performance Optimization of Offshore Sandwich Blast Walls with Different Honeycomb Cores Subjected to Blast Loading - Hong Lin; Chang Han; Lei Yang; Lin Zhang; Haochen Luan; Pingping Han; Hao Xu; Shuo Zhang (Journal of Marine Science and Engineering, 2022)
As an important protective facility on offshore platform, the blast wall is of great significance in resisting oil and gas explosions. Honeycomb structures are widely used due to their unique deformation and mechanical properties under dynamic impact loads. The aim of this research is to develop an optimized design for an offshore sandwich blast wall with different honeycomb cores. The uniqueness of this paper is providing the quantitative optimization scheme for topological configurations and unit cell geometric parameters of honeycomb structures according to mass consistency and the proposed synthetic evaluation index of anti-blast performance. By using the numerical simulation software ANSYS/LS-DYNA, the CONWEP algorithm was first validated and then adopted to conduct the dynamical performance analysis of the honeycomb blast wall. For comparison purposes, simulating studies on a series of different blast walls were carried out by considering various influential parameters. According to different criteria, the blast resistance of the sandwich honeycomb structures was evaluated. It is found that the sandwich plate with concave arc honeycomb core has the best anti-blast performance compared to that of arrow honeycomb core and concave hexagonal honeycomb core. For the concave arc honeycomb structure, the geometric parameters such as concave angle and aspect ratio of honeycomb unit cell have great influence on the blast-resistance performance. Moreover, the concave arc honeycomb structure with positive gradient arrangement has better anti-blast performance than the negative one. The curved blast wall with the curvature of 1/20 achieves better anti-blast performance than the flat blast wall.

Response of microscopical hyperspectral data to past climatic variable - Lingjun Wang; Teng Fei; Meng Bian; Yadan Xu; Haochen Zhang; Yonghong Zheng; Haifeng Zhu (Theoretical and Applied Climatology, 2022)

Dynamic Performance and Crashworthiness Assessment of Honeycomb Reinforced Tubular Pipe in the Jacket Platform under Ship Collision - Hong Lin; Chang Han; Lei Yang; Hassan Karampour; Haochen Luan; Pingping Han; Hao Xu; Shuo Zhang (Journal of Marine Science and Engineering, 2022)
The collision between the pipe legs of jacket platforms and bypassing ships is of great concern for the safety assessment of platforms. Honeycomb structures have been widely used owing to their unique deformation and mechanical properties under dynamic impact loads. In this paper, two typical honeycomb structures, namely hexagonal honeycomb and arrow honeycomb, were constructed for the impact protection of inclined pipe legs in jacket platforms, and the present study aimed to assess the dynamical performance and crushing resistance of the designed honeycomb reinforced structure under ship collision by using the numerical simulation software ANSYS/LS-DYNA. The dynamical performance of the honeycomb reinforced pipe leg was investigated considering various influential parameters, including the impact velocity and impact direction. The crashworthiness of the two types of honeycomb was evaluated and compared by different criteria, namely the maximum impact depth (δmax), specific energy absorption (SEA) and the proposed index offset sliding (OS). The results demonstrated that both the hexagonal honeycomb structure and the arrow honeycomb structure can reduce the damage of inclined pipe legs caused by ship collision, while the hexagonal honeycomb can provide the better anti-collision capacity, which can well reduce the offset sliding and better protect the pipe leg from ship collision.

Generation and management of waste electric vehicle batteries in China - ChengJian Xu; Wenxuan Zhang; Wenzhi He; Guangming Li; Juwen Huang; Haochen Zhu (Environmental Science and Pollution Research, 2017)